2015
DOI: 10.1111/jop.12383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of morbid obesity and bariatric surgery on antioxidant/oxidant balance of the unstimulated and stimulated human saliva

Abstract: In morbid obesity, reduced unstimulated and stimulated salivary flow can be observed. Bariatric surgery restored only unstimulated salivary flow to normal values. Disturbances in oxidant/antioxidant homeostasis may be observed in UWS and SWS of obese patients before and after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 32 publications
3
55
0
6
Order By: Relevance
“…Antioxidants not only inhibit ROS-induced oxidation but also repair some forms of oxidative modification in biomolecules. The most important blood antioxidants include superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), reduced glutathione (GSH) and uric acid (UA) [7,8,11]. It is suggested that antioxidant supplementation could reduce metabolic disorders and improve the condition of obese patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants not only inhibit ROS-induced oxidation but also repair some forms of oxidative modification in biomolecules. The most important blood antioxidants include superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), reduced glutathione (GSH) and uric acid (UA) [7,8,11]. It is suggested that antioxidant supplementation could reduce metabolic disorders and improve the condition of obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact reason for these changes is still unknown. It is postulated that the improvement of obese patients is associated with the reduction of oxidative stress levels [7,8,11]; however, there is no longitudinal data about the redox homeostasis of patients undergoing bariatric treatment. Therefore, the aim of our study was to evaluate the impact of morbid obesity as well as huge weight loss on the blood antioxidant systems/oxidative stress before as well as one, three, six and twelve months after bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Diversas comorbidades são associadas a obesidade, como a hipertensão arterial, diabetes Mellitus tipo II, arteriosclerose, artrite, síndrome da apneia do sono, disfunções endócrinas, câncer, problemas psicossociais, econômicos e problemas bucais. Dentre as principais manifestações bucais pode-se citar periodontite, xerostomia, cárie dentária e lesões erosivas (SAPORITI et al, 2014;KNAS et al, 2016;SALES-PERES et al, 2017).…”
Section: Introductionunclassified
“…Alagoas; E-mail: laisnobree@hotmail.com; (3) Professor de Odontologia e do Mestrado Profissional Pesquisa em Saúde do Centro Universitário CESMAC; (4) Pós-doutorando da Faculdade de Odontologia de Ribeirão Preto da Universidade de São Paulo; E-mail: rodrigoneves.rn@hotmail.com; (5) Professor de Odontologia e do Mestrado Profissional Pesquisa em Saúde do Centro Universitário CESMAC; E-mail: diego_duke@hotmail.com; (6) Doutoranda, Faculdade de Odontologia São Leopoldo Mandic, Campinas, São Paulo; E-mail: sylalbuquerque@hotmail.com; (7) Professor de Odontologia e do Mestrado Profissional Pesquisa em Saúde do Centro Universitário CESMAC; Professor da disciplina de Cariologia da Faculdade de Odontologia da Universidade Federal de Alagoas; E-mail: nbs.odonto@hotmail.com Todo o conteúdo expresso neste artigo é de inteira responsabilidade dos seus autores.…”
unclassified
See 1 more Smart Citation